2011
DOI: 10.1152/japplphysiol.00917.2010
|View full text |Cite
|
Sign up to set email alerts
|

High dietary salt intake increases carotid blood pressure and wave reflection in normotensive healthy young men

Abstract: Dietary salt intake is associated with high brachial blood pressure (BP) and increased risk of cardiovascular disease. We investigated whether changes in dietary salt intake are associated with changes in central BP and wave reflection in healthy volunteers. Ten healthy normotensive male volunteers (22-40 yr) participated in a 6-wk double-blind randomized crossover study to compare a low-dietary salt intake (60-80 mmol sodium/day) with a high-salt intake (low salt intake supplemented with 128 mmol sodium/day) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
(26 reference statements)
1
22
1
Order By: Relevance
“…The increase in cSBP observed in our YG group is in agreement with Starmans-Kool et al [16], who also reported an increase in cSBP in normotensive, healthy young men after a high sodium diet. The present study also reports data on a MA group, providing information on a larger age range.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in cSBP observed in our YG group is in agreement with Starmans-Kool et al [16], who also reported an increase in cSBP in normotensive, healthy young men after a high sodium diet. The present study also reports data on a MA group, providing information on a larger age range.…”
Section: Discussionsupporting
confidence: 93%
“…It appears the increases in forward and reflected wave amplitudes are contributing to the larger augmentation of cSBP observed in the MA group. It should be noted that Starmans-Kool et al [16] reported increased reflected wave amplitudes following a high sodium diet in young, healthy males. We have also demonstrated that the CSBP response to dietary sodium appears to be greater in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many North American Indigenous populations continue to experience food insecurity and limited access to quality foods [37][38][39]. These limitations in diet, and increase in processed foods may lead to increased salt intake, altering blood pressure [37,39,40]. Further, less physically active lifestyles and experiences of racism may also influence blood pressure among Indigenous populations [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Increased arterial stiffness and wave reflection are independent predictors of cardiovascular events [7-11]. Acutely, a high sodium meal has been shown to increase augmentation index in normotensive adults [12] while two weeks of a high salt intake in young, healthy, normotensive males increased wave reflection and carotid BP [13]. Further, two weeks of dietary sodium restriction improved carotid arterial compliance and augmentation index in older individuals with systolic hypertension [14].…”
Section: Introductionmentioning
confidence: 99%